Status of physical activity in the Japanese population - Shigeho Tanaka (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Physical activity surveillance at a population level is important. The National Health and Nutrition Survey of Japan has been carried out annually, and two kinds of assessments for physical activity are included in the survey: total step counts per day, measured by a pedometer, and questions on exercise habits. From peak values seen in 1998 - 2000, time trends display a decline of age-adjusted mean steps per day, and the average percentage of regular exercisers has increased only in the age group of 50 years old or higher. As for standard or target values of physical activity, the Dietary Reference Intakes (DRIs) for Japanese presents standard values of physical activity levels (total energy expenditure divided by basal metabolic rate) for each gender and age group. The moderate value of physical activity level for adults is 1.75. Furthermore, the Exercise and Physical Activity Guide for Health Promotion 2006 (Exercise Guide 2006) was released based on the "Exercise and Physical Activity Reference for Health Promotion 2006" (EPAR2006). The reference values were set as 23 MET-hours/week for physical activity and 4 MET-hours/week for exercise. The former value is equivalent to 8000 to 10000 daily steps. Thus, Japan has established target values for physical activity and exercise habits, and daily steps have been investigated in the Japanese population. However, the target or standard values of physical activity are not sufficiently linked to the nationwide surveillance of actual levels of physical activity. Therefore, development of physical activity evaluation methods for Japanese is necessary.